Resolution of component proteins in an enzyme complex from Methanosarcina thermophila catalyzing the synthesis or cleavage of acetyl-CoA. - Abbanat, D R (1991)
An enzyme complex was isolated from acetate-grown Methanosarcina thermophila that oxidized CO and catalyzed the synthesis or cleavage of acetyl-CoA. The complex consisted of five subunits (alpha1beta1gamma1delta1epsilon1) of 89, 71, 60, 58, and 19 kDa. The complex contained nickel, iron, acid-labile sulfide, and cobalt in a corrinoid cofactor. Two components were resolved by anion-exchange chromatography of the complex in the presence of dodecyltrimethylammonium bromide and Triton X-100: a 200-kDa nickel/iron-sulfur protein with the 89- and 19-kDa (alpha2epsilonx) subunits and a 100-kDa corrinoid/iron-sulfur protein with the 60- and 58-kDa subunits (gamma1delta1). The nickel/iron-sulfur component contained 0.21 Ni, 2.7 Zn, 7.7 Fe, and 13.2 acid-labile sulfide (per alpha1epsilon1). The corrinoid/iron-sulfur component contained 0.7 Co, 0.7 factor III [Coalpha-[alpha-(5-hydroxybenzimidazolyl)]-Cobeta-cyanocobamide], 3.0 Fe, and 2.9 acid-labile sulfide (gamma1delta1). Both components contained iron-sulfur centers. The nickel/iron-sulfur component oxidized CO and reduced methyl viologen or a ferredoxin isolated from M. thermophila. The nickel/iron-sulfur component also oxidized CO and transferred electrons to the corrinoid/iron-sulfur component, reducing the iron-sulfur and Co centers. UV-visible spectroscopy indicated that the reduced corrinoid/iron-sulfur component could be methylated with CH3I. The results suggest that the enzyme complex from M. thermophila contained at least two enzyme components, each with a specific function. The properties of the component enzymes support a mechanism proposed for acetyl-CoA synthesis (or cleavage) by the enzyme complex.